[3+2]-Annulation of oxindolinyl-malononitriles with Morita–Baylis–Hillman acetates of nitroalkenes for the regio- and diastereoselective synthesis of spirocyclopentane-indolinones. (26th February 2022) - Pareek, Abhishek; Sivanandan, Sudheesh T.; Bhagat, Shweta; Namboothiri, Irishi N.N.
Abstract: 3-Oxindolinyl-malononitrile participates as a 1, 2-binucleophile in a highly regio- and stereoselective [3 + 2] annulation with 1, 3-bielectrophilic nitroallylic acetates leading to spirocyclopentane-indolinones. The reaction takes place in the presence of DABCO in THF at room temperature and affords the multi-functional spirocyclic compounds possessing three chiral centers, including a spiro-chiral center in good to excellent yields and short reaction time. The key role of the malononitrile moiety in controlling the reactivity and selectivity has also been demonstrated. An SN 2′-intramolecular Michael addition pathway is proposed for the [3 + 2] annulation based on DFT calculation results. Graphical abstract: To create your abstract, type over the instructions in the template box below.Fonts or abstract dimensions should not be changed or altered. Image 1 Highlights: Spiro-oxindole moiety is an integral part of numerous bioactive molecules including natural products such as alkaloids. Synthesis of cyclopentane linked spiro-oxindoles possessing multiple chiral centers with regio- and stereo control. DABCO mediated [3 + 2]-annulation of oxindolinyl-malononitrile with Morita-Baylis-Hillman (MBH) acetates of nitroalkenes. 1, 2-Binucleophilic character of oxindolinyl-malononitrile has been investigated. The possible reaction pathway is supported by DFT calculations as well.